A high humidity-resistive triboelectric nanogenerator via coupling of dielectric material selection and surface-charge engineering. Issue 37 (9th September 2021) - Liu, Lu; Zhou, Linglin; Zhang, Chuguo; Zhao, Zhihao; Li, Shaoxin; Li, Xinyuan; Yin, Xing; Wang, Jie; Wang, Zhong Lin
Abstract : Dielectric material selection coupled with surface-charge engineering is demonstrated to effectively improve the output performance of triboelectric nanogenerators in a high humidity environment. Abstract : Triboelectric nanogenerators (TENGs) have been demonstrated as a revolutionary energy-harvesting technology toward distributed energy sources and self-powered systems; however, their output performance is significantly affected by humidity, which seriously limits their adaptability and commercialization. Here, we propose a strategy to improve the output performance of TENGs in a high humidity environment by coupling dielectric material selection and surface-charge engineering. The results show that higher surface charges can be achieved by increasing the hydrophobicity of dielectric materials, especially under high humidity. More importantly, it is found that ionic charges are more stable compared with electronic charges under humid conditions. Through utilizing the hydrophobic dielectric material of polytetrafluoroethylene (PTFE) and the ion injection strategy, a TENG retains ∼91% of its initial output performance after 50 000 operation cycles under 90% relative humidity. This work not only provides a paradigm technique to realize high humidity-resistive TENGs, but also opens a promising avenue toward expanding their practical application scope.